Microbiomics for enhancing electron transfer in an electrochemical system - Roy, Ayush Singha; Sharma, Aparna; Thapa, Bhim Sen; Pandit, Soumya; Lahiri, Dibyajit; Nag, Moupriya; Sarkar, Tanmay; Pati, Siddhartha; Ray, Rina Rani; Shariati, Mohammad Ali; Wilairatana, Polrat; Mubarak, Mohammad S. (Frontiers in Microbiology, 2022)
Microorganisms catalyze chemical reactions, thus converting chemical energy present in organic and inorganic molecules into electrical energy in microbial electrochemical systems. The concept of microbial electrochemistry has been gaining attention for the past two decades, mainly due to its numerous applications. This technology offers the potential for implementations in a range of fields such as the environment, industries, and sensors. Biocatalysts governing the reactions are electroactive bacteria, which can interact with insoluble materials such as electrodes for exchanging electrons. Colonization and biofilm formation are generally aided by the exopolysaccharide (EPS) produced during biofilm formation. Though biofilm formation is one of the major modes of bacteria for electron transfer with the electrode, there are other few mechanisms through which the process can occur. The present article covers the literature pertaining to microbiome-induced electron transfer activity, proteins, and secretory molecules involved in the electron transfer. The present work also involves summarizing the literature related to the proteomics and genomics approaches in electroactive bacteria for improving the performance in microbial electrochemical cells. Recent progress and reports on synthetic biology and genetic engineering in enhancing electron transfer activities will be highlighted.